Staffing the National Security Council: How Presidential Management Styles Shape the Composition of the NSC. Issue 3 (21st May 2021) - LaGattuta, Dean; Limbocker, Scott
Abstract: We examine how presidential management styles shape personnel on the National Security Council (NSC). We analyze presidential directives from Presidents Carter to Obama to categorize administrations as either "Hands‐Off" or "Hands‐On" managers of the NSC. Using Office of Personnel Management records, we construct a panel of all NSC employees. We find evidence of Hands‐Off presidents favoring administrative staffs with higher levels of graduate education. Also, across the period considered, there has been a decline in previous government service for those working on the NSC. Finally, we find no evidence management style helps explain the exit decisions of NSC staffers.